Antidiarrhoeal Activity of Terminalia catappa Linn. Leaf Extracts in Rats - SWAMY B.M., VRUSHABENDRA; MANSOORAHMED, SYED; GoPKUMAR, P.; DHANAPAL , R.; CHANDRASHEKAR, Y.M.; SREENIVAS RAO, T. (Asian Journal of Chemistry, 2010)
The methanol, water and petroleum ether extracts of Terminalia catappa Linn were screened for their antidiarrhoeal potential at dose level of 1/5th of their lethal doses screened against several experimental models of diarrhoea in rats. The methanol and aqueous extracts showed significant inhibitory activity against castor oil induced diarrhea and inhibited PGE2 induced enteropooling in rats. The methanol and aqueous extracts also showed significant reduction in gastrointestinal motility following charcoal meal in rats.